Lysophospholipids and Their G-Coupled Protein Signaling in Alzheimer’s Disease: From Physiological Performance to Pathological Impairment - Hao, Yining; Guo, Min; Feng, Yiwei; Dong, Qiang; Cui, Mei (Frontiers in Molecular Neuroscience, 2020)
Lysophospholipids (LPLs) are bioactive signaling lipids which are generated from phospholipase-mediated hydrolyzation of membrane phospholipids (PLs) and sphingolipids (SLs). Lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) are two of the best-characterized LPLs which mediate a variety of cellular physiological responses via specific G-protein coupled receptor (GPCR) mediated signaling pathways. Considerable evidence now demonstrates the crucial role of LPA and S1P in neurodegenerative diseases, especially in Alzheimer's disease (AD). Dysfunction of